2022
DOI: 10.1021/acs.macromol.1c02329
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Charge Transport of P(NDI2OD-T2) by Improving the Polarization of the NDI2OD Unit along the Backbone Direction and Preaggregation via H-Bonding

Abstract: The charge transport of donor−acceptor (D−A) conjugated polymer along the intramolecular main chain is faster than the intermolecular π−π stacking. The higher the backbone coplanarity is, the more efficient the charge transport is. Here, we proposed a strategy to improve the backbone planarization by increasing the polarization of the A unit along the main chain direction via hydrogen-bonding (H-bonding) interactions. This is enabled by adding ethylene glycol (EG) to poly{[N,N′-bis(2octyldodecyl)-naphthalene-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…This trend might attribute to the less content of conjugated segments, which leads to less π–π interaction and aggregation. Next, the aggregate fractions of the polymers were evaluated by deconvoluting the UV–vis absorption profiles of the polymer films and polymer solutions in 1-chloronaphthalene (CN, 0.05 mg/mL), representing the disorder profile. The deconvolutions of UV–vis absorption spectra are presented in Figure S24, and the comparison between aggregate fractions of the polymers is presented in Figure c. As can be seen, the aggregate fractions of the polymers are 26.3/25.2% for S1 / S2 , 29.2/26.2% for C1 / C2 , and 29.5/27.4% for O1 / O2 .…”
Section: Resultsmentioning
confidence: 99%
“…This trend might attribute to the less content of conjugated segments, which leads to less π–π interaction and aggregation. Next, the aggregate fractions of the polymers were evaluated by deconvoluting the UV–vis absorption profiles of the polymer films and polymer solutions in 1-chloronaphthalene (CN, 0.05 mg/mL), representing the disorder profile. The deconvolutions of UV–vis absorption spectra are presented in Figure S24, and the comparison between aggregate fractions of the polymers is presented in Figure c. As can be seen, the aggregate fractions of the polymers are 26.3/25.2% for S1 / S2 , 29.2/26.2% for C1 / C2 , and 29.5/27.4% for O1 / O2 .…”
Section: Resultsmentioning
confidence: 99%
“…This situation should be carefully contrasted with the convention in polymer solution and rheology sciences that assigns the solvent mobility or viscosity to dissipative forces, which have long been believed to be unrelated to the determination of solvent quality. Recent experiments , and computer simulation on a closely related phenomenon of chain foldingor self-aggregationfor a widely studied crystalline conjugated copolymer, P­(NDI2OD-T2) (poly­{[( N , N ′-bis­(2-octyldodecyl)-naphthalene-1,4,5,8-bis­(dicarboximide)-2,6-diyl]- alt -5,5′-(2,2′-bithiophene)})), in various solvent media have ubiquitously identified 1-chloronaphthalene (CN) as an excellent solvent (i.e., nearly no chain folding) as compared to toluene (i.e., prevalence of chain folding). Although the polymer–solvent interactions in the two solvent systems of P­(NDI2OD-T2) remain unexplored, the substantially higher viscosity (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the mechanistic features by which different types of solvent media dictate the solubility and aggregation (or crystallinity) properties of crystalline conjugated polymers, such as the widely studied polythiophene series as of 2022, can greatly facilitate the advance of contemporary science and technology on organic photovoltaic cells (OPVs) and organic field-effect transistors (OFETs). Often, solvent media that offer tolerable solubility in these applications are classified into two categories: better solvents that yield good nominal solubility but poor crystallinity and poorer solvents that help promote the crystallinity at the cost of polymer solubility. , The interesting compromise between the two types of solvent media in light of their overall impact on the performance of the devices so fabricated has since motivated a continued search for optimal solvent media in current applications with crystalline conjugated polymers. , From a scientific perspective, the origins and mechanistic features of solvent quality remain elusive in general. Although there have been many experimental studies ,, that offer illuminating insights into these issues, no definite physical picture has yet been reached that can clearly explain the thermodynamics and kinetics dictating the initial stage of solvation and association when solvent quality changes, which would eventually lead to the bulk aggregation state measurable by conventional experimental schemes.…”
Section: Introductionmentioning
confidence: 99%
“…We also note that few studies have reported µ e > 1 cm 2 V -1 s -1 in the TGBC configuration with the required alignment and solution aggregation. [46][47][48] Therefore, for solution processing, TGBC structures were chosen to facilitate the coating of polymer dielectrics because it is easy to find orthogonal solvents for polymer semiconductors rather than polymer dielectrics. However, the possibility of physical or chemical deterioration caused by the solvent cannot be eliminated.…”
Section: Ofet Characteristicsmentioning
confidence: 99%